Exploring fathers' experience of their first child's early years: Representations versus reality - Chacin, Margarita; McBeath, Alistair (European Journal for Qualitative Research in Psychotherapy, 2023)
This qualitative study explored fathers’ lived experience and meanings of being a first-time father in the United Kingdom. Seven fathers were interviewed, and the resulting data were analysed using Interpretative Phenomenological Analysis (IPA). Two main categories emerged from the analysis: The first captures how fathers’ experiences developed over time concerning: i. how becoming a father was a “natural way of being”; ii. how they were confronted with the differences between reality and their expectations; iii. how they described traditional fatherhood and the compulsory equality in parenting; and iv. about their willingness to be involved as a modern father. The second master theme describes the challenges faced by fathers including how fathers: i. cope with tiredness; ii. have undesirable feelings, including fear, worry and uncertainty; iii. lack acknowledgement and feel some resultant shame; and iv. experience guilt when they were not physically present for their children. This research discusses the impact of both their understandings (including representations) of fatherhood and how fatherhood is subjectively experienced. It is recommended that therapists attend to these changing experiences in order to offer appropriate psychotherapeutic approaches and tools to fathers.